2023
DOI: 10.1002/advs.202301309
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular Bioprinting of Biomimetic Inks for Tendon‐to‐Bone Regeneration

Abstract: Tendon‐to‐bone interface has a hierarchical structure and gradient component that are conducive to distributing the stresses to achieve movement. Conventional biomaterials lack the capacity to induce synchronous repair of multiple tissues, resulting in the failure of the interface repair. Biomimetic strategies have attracted enormous attention in the field of complex structure regeneration because they can meet the different physiological requirements of multiple tissues. Herein, a biomimetic ink mimicking ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Currently, multicellular 3D-bioprinting technique has emerged as an attractive strategy to construct heterogeneous biomimetic trachea with native-like tissue architecture [ [40] , [41] , [42] , [43] ]. To date, there is still limited breakthrough to realize segmental trachea reconstruction using 3D-bioprinted biomimetic trachea.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, multicellular 3D-bioprinting technique has emerged as an attractive strategy to construct heterogeneous biomimetic trachea with native-like tissue architecture [ [40] , [41] , [42] , [43] ]. To date, there is still limited breakthrough to realize segmental trachea reconstruction using 3D-bioprinted biomimetic trachea.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes promoted the expression of Scx and SOX-9 [ 77 , 86 , 87 ], which were reported to regulate the differentiation of progenitor cells and promote the establishment of cell phenotype gradients of the tendon–bone interface [ 22 , 129 ]. Multiple studies have reported that the hedgehog proteins and the hedgehog signaling pathway played a significant role in the reconstruction of the tendon–bone interface gradient [ 130 , 131 , 132 ]. However, no studies have reported whether there is a regulatory relationship between exosomes and hedgehog proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biomaterials with hierarchical structures are widely developed for repairing the tendon-to-bone interface. A biomimetic nanofiber scaffold was successfully constructed to simulate the microstructure of the tendonbone interface [154] . The curly microstructure mimicked the natural tendon-bone interface ECM, promoting cartilage generation at the interface area.…”
Section: Hierarchical Tissue Regenerationmentioning
confidence: 99%